Potential use of urban sewage sludge as an energy source (Research, Society and Development, 2025)
The sewage sludge is a potential economic and environmental problem in Brazil, since its disposal is mostly carried out in landfills. Using this waste as a source of energy, in addition to promoting a sustainable and efficient strategy for generating clean energy, also acts as a source of support for the basic sanitation sector. Thus, the study aimed to evaluate the energy potential of raw and pyrolyzed sewage sludge through the Higher Calorific Value (HCV). An exploratory, laboratory study of a quantitative nature was carried out. The analyses were performed duplicate with the aid of the IKA C-200 calorimetric bomb, using the average values obtained for each material. Analyzing the results obtained, average values of 20.07 and 10.13 MJ.kg-1 were observed for the raw and carbonized samples, respectively. These values corroborate those found in literature for materials already consolidated in energy generation, such as wood, for example. Thus, it is concluded that urban sewage waste can be used for energy purposes with emphasis on its use in its direct form in natura.